Active metabolites of the genus Piper against Aedes aegypti: natural alternative sources for dengue vector control - Marques, Andre (2014)
The mosquito, Aedes aegypti, is the principal vector of the viruses responsible for dengue and dengue hemorrhagic fevers. The mosquito is widespread throughout tropical and sub-tropical regions; its prevalence makes dengue one of the most important mosquito-borne viral diseases in the world occurring annually in more than 100 endemic countries. Because blood is essential to their development cycle, the Aedes species maintains a close association with humans and their dwellings. Fittingly, the most widely adopted strategy to decrease the incidence of these diseases is the control of the mosquito larvae population. The emergence of insecticide-resistant mosquitoes has amplified the interest in finding natural products effective against Aedes aegypti adults, as well as larvae. Plant-derived compounds have played an important role in the discovery of new active entities for vector management as they are safer and have lower toxicity to humans in comparison to conventional insecticides. This review assesses a naturally occurring plant matrix and pure compounds of the Piper species, which have been shown to be active against Aedes aegypti.